A director's approach planning a scene with Tom Jerry (North Ryde, NSW. : Australian Film Television & Radio School, 1982)
Tom Jerry, TV director/producer, reviews the role of the director in interpreting the script and translating it to the screen
Production assistant, Bronwyn Walker
Keywords: Motion pictures -- Setting and scenery